La flexibilidad laboral en España y Perú: análisis de ciertos aspectos diferenciadores - Quiñones, Sergio Arturo (2012)
Labor flexibility in Spain and Peru: Analysis of somedifferential aspectsThis paper contains a comparative analysis of the labor flexibility processes held in the past decades both in Spain and Peru, trying to identify the most relevant differential aspects between them based on the following three factors: (i) the existence —or not— of a political framework; (ii) the labor markets particularities that influence the regulation of the individual labor contracts; and (iii) the potential of unions and collective bargaining